2022
DOI: 10.1186/s13075-022-02797-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging characteristics in patients with spondyloarthritis and clinical diagnosis of heel enthesitis: post hoc analysis from the phase 3 ACHILLES trial

Abstract: Objective To investigate the imaging characteristics and clinically assess heel enthesitis in spondyloarthritis (SpA) by applying in a post hoc analysis the Heel Enthesitis Magnetic Resonance Imaging Scoring system (HEMRIS) in blinded and centrally-read MRI data from the ACHILLES trial (NCT02771210). Methods ACHILLES included patients (≥18 years) with active psoriatic arthritis or axial SpA with clinical and MRI-positive heel enthesitis refractory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The MRI study of patients belonging to the ACHILLES trial confirmed the central role of this technique also in the study of heel enthesitis. In particular, the authors observed more evident pathologies in the Achilles tendon area than in the plantar aponeurosis; moreover, it was observed that the most frequent lesions were intra-tendon hypersignal and retrocalcaneal bursitis (43).…”
Section: Imagingmentioning
confidence: 96%
“…The MRI study of patients belonging to the ACHILLES trial confirmed the central role of this technique also in the study of heel enthesitis. In particular, the authors observed more evident pathologies in the Achilles tendon area than in the plantar aponeurosis; moreover, it was observed that the most frequent lesions were intra-tendon hypersignal and retrocalcaneal bursitis (43).…”
Section: Imagingmentioning
confidence: 96%